Financial Market Integration In Asia: Evidence From Stock And Bond Market - Fauziah Fauziah (University of Islam Malang, 2018)
Financial integration especially in Asian financial market has been a defining feature of the world economy and has become a central issue in international finance for the past decades. However, there is limited empirical studies on the integration of Asian bond market. Therefore, this study aims to examine the financial market integration in Asia (Stock and Bond Market). The sample of this study is the major of Asian financial markets including Japan, China, Hong Kong, Singapore and South Korea during January 2009 – December 2016. Correlation, co-integration and causality tests used in this study to investigate the financial markets integrations. This study shows that both stock and bond returns are co-integrated and indicate as a common stochastic trends. Stock market integration appears to be much stronger compared to the less developed. This result is very important for investors to assess potential gains from portfolio diversification, and for a financial policymaker to manage market policies effectively and handle contagion risks that might be caused by international shock transmissions.